Does binge drinking between the age of 18 and 25 years predict alcohol dependence in adulthood? A retrospective case–control study in France. Issue 5 (5th May 2019) - Tavolacci, Marie-Pierre; Berthon, Quentin; Cerasuolo, Damiano; Dechelotte, Pierre; Ladner, Joel; Baguet, Alexandre
Abstract : Objective: A retrospective case–control study was conducted to evaluate whether frequent binge drinking between the age of 18 and 25 years was a risk factor for alcohol dependence in adulthood. Setting: The Department of Addictive Medicine and the Clinical Investigation Center of a university hospital in France. Participants: Cases were alcohol-dependent patients between 25 and 45 years and diagnosed by a psychiatrist. Consecutive patients referred to the Department of Addictive Medicine of a university hospital between 1 January 2017 and 31 December 2017 for alcohol dependence were included in the study. Controls were non-alcohol-dependent adults, defined according to an Alcohol Use Disorders Identification Test score of less than 8, and were matched on age and sex with cases. Data on sociodemographics, behaviour and alcohol consumption were retrospectively collected for three life periods: before the age of 18 years; between the age of 18 and 25 years; and between the age of 25 and 45 years. Frequency of binge drinking between 18 and 25 years was categorised as frequent if more than twice a month, occasional if once a month and never if no binge drinking. Results: 166 adults between 25 and 45 years were included: 83 were alcohol-dependent and 83 were non-alcohol-dependent. The mean age was 34.6 years (SD: 5.1). Frequent binge drinking between 18 and 25 years occurred in 75.9% of cases and 41.0% of controls (p<0.0001). After multivariate analysis, frequent binge drinking between 18 and 25 years was a risk factor for alcohol dependence between 25 and 45 years: adjusted OR=2.83,  95% CI 1.10 to 7.25. Conclusions: Frequent binge drinking between 18 and 25 years appears to be a risk factor for alcohol dependence in adulthood. Prevention measures for binge drinking during preadulthood, especially frequent binge drinking, should be implemented to prevent acute consequences as injury and death and long-term consequences as alcohol dependence. Trial registration number: NCT03204214 ; Results.